2022
DOI: 10.1007/s42761-021-00083-5
|View full text |Cite
|
Sign up to set email alerts
|

Reading Your Emotions in My Physiology? Reliable Emotion Interpretations in Absence of a Robust Physiological Resonance

Abstract: Affective states are expressed in an individual’s physical appearance, ranging from facial expressions and body postures, to indicators of physiological arousal (e.g., a blush). Confirming the claimed communicative function of these markers, humans are capable of distinguishing between a variety of discrete emotion displays. In an attempt to explain the underlying mechanism, characteristic bodily changes within the observer, including physiological arousal and mimicry, have been suggested to facilitate the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…However, the fact that we observed a comparable effect of stimulus intensity between the two types of emotions in the discrimination task but not in the temporal task raises some questions along with a limit of the present study. It has been shown that there is no unique relationship between emotional discrimination and physiological responses (Folz et al 2022 ), which differ depending on the emotional type. Since we do not have direct measures of physiological responses associated with arousal, our conclusions on the emotional distortion of time perception are limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that we observed a comparable effect of stimulus intensity between the two types of emotions in the discrimination task but not in the temporal task raises some questions along with a limit of the present study. It has been shown that there is no unique relationship between emotional discrimination and physiological responses (Folz et al 2022 ), which differ depending on the emotional type. Since we do not have direct measures of physiological responses associated with arousal, our conclusions on the emotional distortion of time perception are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to subjective verbal reports on the effect of the stimuli (which are however prone to a number of limitations, Guadagni et al., 2019; Pistoia et al., 2015), a number of more objective physiological indices of sensorimotor or affective reactivity to others' pain were obtained. In particular, we collected data regarding: (i) responses involving facial muscles (which are closely connected to sensorimotor responses, Sun et al., 2015), in particular, by means of facial electromyography of the left Corrugator and the Zygomaticus muscles (under the assumption that the former is associated with emotional responses linked to fear, worry and pain, i.e., the experimental condition, and the latter is linked to happy facial expressions, i.e., the control condition); (ii) ElectroDermal Activity (EDA) which is an autonomic index of ortho‐sympathetic activity that is associated with changes in arousal and affective responses (Folz et al., 2022; Ganapathy & Swaminathan, 2019; Polo et al., 2022; Rao Veeranki et al., 2021; Vinberg et al., 2022; Zitouni et al., 2023), and (iii) Respiratory Sinus Arrhythmia (RSA), which is a physiological index related to cardiac parasympathetic tone. The computation of this index is based on the tendency of the heart rate to accelerate during inhalation and to decelerate during exhalation, a phenomenon related to the interaction between the cardiovascular and respiratory systems.…”
Section: Introductionmentioning
confidence: 99%
“…the experimental condition, and the latter is linked to happy facial expressions, i.e. the control condition); ii) ElectroDermal Activity (EDA) which is an autonomic index of ortho-sympathetic activity that is associated with changes in arousal and affective responses (Zitouni et al, 2023;Vinberg et al, 2022;Polo et al, 2022;Folz et al, 2022;Rao Veeranki et al, 2021;Ganapathy & Swaminathan, 2019) and iii) Respiratory Sinus Arrhythmia (RSA) which is an index of parasympathetic activity (calculated with reference to Cardiac activity -pulse pressure waves -and breathing frequency), and is generally associated with basic metabolism activity (Bernston et al, 1993). Furthermore, in keeping with previous studies (e.g.…”
Section: Introductionmentioning
confidence: 99%